Proceedings of SPE European Formation Damage Conference 1999
DOI: 10.2523/54764-ms
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Invert Emulsion Drilling Fluids: Controlling Wettability and Minimizing Formation Damage

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractNovel emulsifiers in reversible invert emulsion drilling fluids offer a unique opportunity for operators to control the wettability properties of the mud. Reversibility of the invert emulsion will provide economic advantages in drilling and completion and increased productivity. Optimal drilling performance and formation damage control are usually achievable by oil wetting the drill solids, formation and drillstring. On the other hand, optimal completion of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…3,84 In those cases, the reversible emulsions are stabilized by surfactant emulsifiers, and the viscosity normally decreases near the transitional point. 4,85,86 However, the smooth transition of the rheological properties at the approximate transitional inversion point seen in our case is crucial for safety in the drilling process, since complex problems such as Barite sedimentation, cuttings suspension, or flow impedance could occur if the emulsion rheology deteriorated and emulsion stability failed. Moreover, both W/ O emulsions and O/W emulsions exhibit reasonable gel structures as well as shear-thinning stability with relatively low viscosity for a base Pickering emulsion, which makes it possible to obtain an entire range of desired properties by adjusting the composition of the drilling fluid through the addition of various agents.…”
Section: Resultsmentioning
confidence: 67%
“…3,84 In those cases, the reversible emulsions are stabilized by surfactant emulsifiers, and the viscosity normally decreases near the transitional point. 4,85,86 However, the smooth transition of the rheological properties at the approximate transitional inversion point seen in our case is crucial for safety in the drilling process, since complex problems such as Barite sedimentation, cuttings suspension, or flow impedance could occur if the emulsion rheology deteriorated and emulsion stability failed. Moreover, both W/ O emulsions and O/W emulsions exhibit reasonable gel structures as well as shear-thinning stability with relatively low viscosity for a base Pickering emulsion, which makes it possible to obtain an entire range of desired properties by adjusting the composition of the drilling fluid through the addition of various agents.…”
Section: Resultsmentioning
confidence: 67%
“…Is there another way for the RIEM to reduce the formation permeability besides plugging the pores? It is generally believed that the surfactants in the oil-based mud that invades the rock matrix are capable of changing the natural wetting state from water-wet to oil-wet, thus impeding the flow of hydrocarbons through the rock matrix during production (Chen et al, 2006;Cuiec, 1989;Gant and Anderson, 1988;McDonald and Buller, 1992;Patel and Growcock, 1999;Skalli et al, 2006;Yan et al, 1993;Yan and Sharma, 1989).…”
Section: Riem Cleanup Characterizationmentioning
confidence: 99%
“…A limited number of publications on this topic can be found in the literature. Several authors (Ali et al, 2004(Ali et al, , 2006Green et al, 2001;Patel, 1999;Patel and Growcock, 1999;Patel and Ali, 2003) reported that low pH promotes the transformation of RIEMs from a water-in-oil type to an oil-in-water type, inducing the water wetting condition of the surfaces of the pipes and the drilled formation. Bryant et al (2006) has demonstrated that the adsorption of ethoxylated alkylamines affects the wettability of mica surfaces.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation